2003
DOI: 10.1152/ajplung.00447.2002
|View full text |Cite
|
Sign up to set email alerts
|

ATP- and UTP-activated P2Y receptors differently regulate proliferation of human lung epithelial tumor cells

Abstract: The involvement of P2Y receptors, which are activated by extracellular nucleotides, in proliferative regulation of human lung epithelial cells is unclear. Here we show that extracellular ATP and UTP stimulate bromodeoxyuridine (BrdU) incorporation into epithelial cell lines. The nucleotide efficacy profile [ATP = ADP > UDP >or= UTP > adenosine >or= 2-methylthioadenosine-5'-diphosphate, with alpha,beta-methylene adenosine 5'-triphosphate, 2',3'-O-(4-benzoylbenzoyl)adenosine 5'-triphosphate, AMP, UMP, and ATPalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 47 publications
3
103
1
Order By: Relevance
“…It is generally believed that intracellular Ca 2+ plays an important role in UTP-induced IL-6 production (28). We demonstrated that BAPTA-AM, an intracellular Ca 2+ chelator, suppressed UTP-induced ERK phosphorylation and IL-6 mRNA expression (Fig.…”
Section: +supporting
confidence: 53%
“…It is generally believed that intracellular Ca 2+ plays an important role in UTP-induced IL-6 production (28). We demonstrated that BAPTA-AM, an intracellular Ca 2+ chelator, suppressed UTP-induced ERK phosphorylation and IL-6 mRNA expression (Fig.…”
Section: +supporting
confidence: 53%
“…It was reported that A549 cells express P2Y2 and P2Y6 purinergic receptors (23,24). We found in this study that ATP γ S markedly augments the migration of TGF β 1 -treated A549 cells (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Tumor cell-derived ATP has been suggested to play roles in tumor cell proliferation (19), intratumoral endothelial leakage (20), and adhesion of tumor cells to LECs (21). Although damaged cell-derived ATP may show favorable effects on anticancer immunity via P2RX7 receptors on dendritic cells (15), direct effects of endogenous ATP on A549 cell via P2Y receptors would be tumor-promoting, by stimulating cell proliferation (23) and migration (present study).…”
Section: Discussionmentioning
confidence: 74%
“…P2X7R expressing HEK cells show increased proliferation, reduced apoptosis and more developed vascular network in vivo with strong P2X7R positivity in several human cancers (Adinolfi et al 2012b). This is contradictory to previous reports indicating a proapoptotic effect of P2X7R in tumour cells (Greig et al 2003, Schafer et al 2003, Wang et al 2004b, White et al 2005, Shabbir & Burnstock 2009). Whether these differences are due to the potential preferential expression of P2X7R variants by different tumour cells is currently not known.…”
Section: P2x7r and Bone Cancercontrasting
confidence: 56%